Anatomical study of the renal veins observed during 342 living-donor nephrectomies - Baptista-Silva, José Carlos Costa (1997)
The anatomical variations of renal veins observed during 342 nephrectomies in living donors are described, 311 cases on the left side and 31 on the right. The following anatomy of the renocava veins was observed: 1. On the left side the renal vein was always unique (311/311) and had two tributaries (suprarenal and gonadal veins) in 100 per cent and one or more renolumbar veins in 65.27 per cent, encircling the aorta in 1.07 per cent, was retroaortic in 1.4 per cent; and the inferior vena cava was double in 0.64 per cent; B- on the right side the renal vein was double in 29 per cent (9/31) and had only one tributary (gonadal vein) in one case, for 3.22 per cent (1/ 31); three or more renal veins in 9.7 per cent (3/31). We concluded that the left renal vein is always unique, presenting variations principally in its tributaries and trajectory. On the right side, the renal vein was double or triple in 38.79 per cent.